National Land Code : a commentary - 182924 Sihombing, Judith (Kuala Lumpur : Malayan Law Journal, 2004)
Vol. 1. Historical and other background matters, Commentary on the National Land Code section 1 to 157B -- Vol. 2. Commentary on the National Land Code section 158 to 291 -- Vol. 3. Commentary on the National Land Code section 292 to 447, Penang and Malacca, Personal law